The Zero Divisor Graph of the Ring Z_(2^2 p) - Shuker, Nazar H.; Rashed, Payman A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
In this paper, we consider the crossing number and the chromatic number of the zero divisor graph Γ(Z_(2^2 p)) to show that this type of zero divisor graphs is bipartite graph, and the smallest cycle in Γ(Z_(2^2 p)) is of length four this implies that the girth is equal four.